Sintesis Dan Karakterisasi Kertas Berbahan Dasar Kulit Pisang Kepok Dan Kulit Durian - Pasaribu, Adella Ayu Putri; Daulay, Abdul Halim; Husnah, Miftahul (Rekayasa Material, Manufaktur dan Energi, 2025)
Research has been carried out which aims to find out whether paper can be produced from kepok banana peels and durian peels, as well as knowing the characteristics of the paper produced and the optimum variations. The materials used for Kepok banana peels and durian peels are waste from Kepok banana peels and durian peels that are no longer used. Variations in the composition of Kepok banana peel and durian peel used include 30:70 (sample A), 50:50 (sample B), 70:30 (sample C). The characteristics of this research are grammage test, tensile resistance test, tensile strength test, water content test, and (SEM) test. The research results showed that the grammage test results for sample A were 56.66 g/m², sample B was 53.33 g/m², sample C was 50.33 g/m². The tensile resistance test value for sample A is 2.218MPa, sample B is 0.247MPa, sample C is 1.074 MPa. The tensile strength test value for sample A was 0.37%, sample B was 0.29%, and sample C was 0.35%. The water content test value for sample A was 5.1%, sample B was 1.5%, and sample C was 4.3%. The optimum characteristics found in sample A are variations in mixing kepok banana peel and durian peel 30:70.